2010
DOI: 10.1111/j.1749-6632.2009.05373.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering of skin and cornea

Abstract: Human beings are greatly preoccupied with the unavoidable nature of aging. While the biological processes of senescence and aging are the subjects of intense investigations, the molecular mechanisms linking aging with disease and death are yet to be elucidated. Tissue engineering offers new models to study the various processes associated with aging. Using keratin 19 as a stem cell marker, our studies have revealed that stem cells are preserved in human skin reconstructed by tissue engineering and that the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Studies by Luo et al showed that isolated HUCB stem cells could enhance the healing of mice skin defect wounds, and it was found that the implanted HUCB stem cells could differentiate into keratinocytes in the wound tissue [222]. Cultured ADSCs can also contribute to wound healing and can be added to engineer a trilayered skin substitute featuring the skin's deepest layer, the adipocyte-containing hypodermis, along with both dermis and epidermis [223]. ADSCs secrete various growth factors that control and regenerate damaged skin-type cells, a function that has been termed essential for the regenerative mechanisms of ADSCs [224].…”
Section: Stem Cell-scaffold Constructs For Skin Tissue Engineeringmentioning
confidence: 97%
“…Studies by Luo et al showed that isolated HUCB stem cells could enhance the healing of mice skin defect wounds, and it was found that the implanted HUCB stem cells could differentiate into keratinocytes in the wound tissue [222]. Cultured ADSCs can also contribute to wound healing and can be added to engineer a trilayered skin substitute featuring the skin's deepest layer, the adipocyte-containing hypodermis, along with both dermis and epidermis [223]. ADSCs secrete various growth factors that control and regenerate damaged skin-type cells, a function that has been termed essential for the regenerative mechanisms of ADSCs [224].…”
Section: Stem Cell-scaffold Constructs For Skin Tissue Engineeringmentioning
confidence: 97%
“…Recently, ocular toxicity tests have been increasingly performed with in vitro methods [13]. The authorities have encouraged researchers to develop in vitro studies, for example, the European legislation (Directive 63/2010/EU) is based on replacement, reduction, and refinement of animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the feeder layer-dependent (i3T3) preservation of the growth characteristics of primary cultured skin keratinocytes and both corneal epithelial and endothelial cells also rely on maintaining the stability of the TFs Sp1 and NFI [14][15][16][17]. Both Sp1 and NFI are well known housekeeping transcription factors that each plays a very important role in cell proliferation [31][32][33][34]. Remarkably, i3T3 were proposed to delay terminal differentiation of human skin keratinocytes by preventing the proteosomal degradation of Sp1 and NFI, both of which play pivotal functions during cell cycle progression [14,33,35].…”
Section: Discussionmentioning
confidence: 99%